Processos de pesquisa e de estudo e a formação de professores: alguns aspectos teórico-metodológicos - Del-Masso, Maria Candida Soares [UNESP]; Castro, Rosane Michelli de [UNESP]; Penitente, Luciana Aparecida de Araújo [UNESP] (My University, 2012)
Both the research and the university extension projects and the experiences of the students have an important role for the training of the teachers. Bring these issues of the quotidian aspects in the school to be analyzed by students to favor closer relations between theory and practice considering a specific academics context, historicizing and contextualizing both of them. Added to this, it allows for analyzing didactic issues in the interrelationship between the organizational aspects and the school community aspects. From these aspects, and considering our practice in teaching and researching in the university, we intend to address in this article to analyze theoretical and methodological aspects of research processes and the study aspects which, in our view, are important and add quality in the role of teacher training in both the initial and continuing education. We use the research and the study terms, because we believe that the developments of the both are fundamental to the methodological emphasis of the study process.

Tanto a pesquisa e a extensão universitária como as experiências vivenciadas pelos alunos assumem papel importante para a formação de professores. Trazer as questões do cotidiano escolar para serem analisadas pelos alunos, além de favorecer a aproximação entre a teoria e a prática permite que essas questões didáticas sejam analisadas dentro de um contexto escolar específico, contextualizando e historicizando-as. Acrescido a isso, permite analisar questões do ensino na sua inter-relação com os aspectos organizacionais e com os referentes à comunidade escolar. A partir desses aspectos e considerando nossa prática na docência, pretendemos, neste artigo, abordar aspectos teórico-metodológicos de processos de pesquisa e de estudo que, a nosso ver, importam e agregam em qualidade à formação de professores tanto em nível inicial quanto continuada. Utilizamos os termos pesquisa e estudo, pois acreditamos que para o desenvolvimento de uma pesquisa é fundamental a ênfase metodológica no processo de estudo.
The research and study processes and the role of teacher training: some theoretical and methodological aspects
Keywords: educação; processos de pesquisa; Formação de professores; aspectos Teórico-metodológicos